Sistema de informação da pós-graduação brasileira: avaliação da Plataforma Sucupira - Maria Aniolly Queiroz Maia (2020)
Information systems are tools used in many social contexts. In the educational setting, academic management systems stand out, among which is the ‘Sucupira’ Platform, used for the management, evaluation and transparency of the Brazilian ‘stricto sensu’ Graduate Programme. Considering the relevance of these tools, several fields of knowledge, such as Information Science (CI) and Information Systems (SI), have developed research in this respect, with the SI evaluation being an investigation perspective. Thus, this research has the general objective of evaluating the Data Collection module of the ‘Sucupira’ Platform from the perspective of those responsible for completing it, through an integrative approach of the evaluation methodologies of information systems in the fields of CI and SI. In its theoretical foundation, it addresses the definition, characteristics and evolution of information systems, as well as presenting the ‘Sucupira’ Platform and the modules that compose it, with an investigative focus being the Data Collection module of mandatory use by the managers of the Brazilian ‘stricto sensu’ Graduate Programme. From a bibliographic survey and the establishment of selection criteria, the information systems success model proposed by DeLone and McLean (2003) and the perspective of understanding the needs of the individual proposed by Taylor (1986) as key methodologies were identified for the evaluation of an SI. Thus, based on the selected methodologies, a conceptual IS evaluation model was proposed for the evaluation of the Data Collection module. With regard to the methodology, it can be classed as applied dewscriptive research utilizing a mixed approach. Its population comprised 4,580 ‘stricto sensu’ Graduate Programmes registered on the ‘Sucupira’ Platform, and obtained a survey return of 656 participants, with a self-selective non-probabilistic convenience sample. In the case of data analysis, for objective questions, descriptive statistical analysis, the non-parametric Chi-square test, correlation analysis and exploratory factor analysis using Pearson's matrix were used. In the case of the subjective optional question, Bardin’s (2011) content analysis method was used. Among the various results that comprise the research, a greater concern with the Accessibility, Usability and Interoperability of the SI were seen to be important factors, in addition to the Utility and Precision of the information provided in the evaluated module. In this way, some actions were proposed with a view to better meeting the expectations of the users responsible for completing the ‘Sucupira’ Platform.